New material of Pseudoloris parvulus (Microchoerinae, Omomyidae, Primates) from the Late Eocene of Sossís (northeastern Spain) and its implications for the evolution of Pseudoloris. Issue 83 (June 2015) - Minwer-Barakat, Raef; Marigó, Judit; Femenias-Gual, Joan; Moyà-Solà, Salvador
Abstract: The species Pseudoloris parvulus, identified in several Middle and Late Eocene European sites, was previously known in the Iberian Peninsula by a single mandible preserving P4 –M3 from Sossís (Southern Pyrenean Basins, northeastern Spain), described in the 1960s. Further field work at this Late Eocene site has led to the recovery of a large number of mammal remains, including the additional material of P. parvulus described in this paper. Some specimens of P. parvulus from this locality have also been recently found in the collections of the Naturhistorisches Museum Basel, Switzerland. The whole sample consists of 11 mandible fragments including several teeth, three upper dental series and nearly 80 isolated teeth including all of the dental elements, and represents the most complete sample of the genus described from the Iberian Peninsula. This abundant material allows us to provide an emended diagnosis for the species and to observe several directional changes in the dental morphology of the lineage including the species Pseudoloris saalae, Pseudoloris isabenae, Pseudoloris pyrenaicus and P. parvulus . These directional changes include the progressive reduction of the paraconid in the lower molars and the increase in size of the hypocone, metaconule and paraconule in the upper molars. Moreover, despite the overall resemblance among all of the samples ascribed to P. parvulus, we also recognize some differences, particularly an increase in size and better development of the hypocone from the oldest populations of the species, such as Le Bretou, to the most recent ones, like Sossís and Perrière. Therefore, this study sheds new light on the evolution of this genus, which inhabited Europe from the Middle Eocene to the Early Oligocene.